Factors Associated with Abdominal Obesity among Reproductive Age Women of Kaski District - Tripathi, Narayan; Parajuli, Bijaya; Koirala, Arun Kumar; Joshi, RojanaDhakal (Journal of Karnali Academy of Health Sciences, 2022)
Background: Obesity is increasing at an alarming rate and has now become a global public health problem. Reproductive age women who are obese are at increased risk of infertility, miscarriage and other adverse pregnancy outcomes. The risk of fetal anomalies and congenital heart disease could too increase in offspring of such women. In view of these considerations, this study aimed to assess the factors associated with abdominal obesity among reproductive age women of Kaski district. Method: An analytical cross-sectional study was conducted in Kaski district among 276 reproductive aged women. The association between abdominal obesity and the explanatory variables were assessed in both bivariate and multivariate analysis. Results: More than two third (69.6%) of the respondents were abdominally obese as per waist circumference and the prevalence of abdominal obesity as per Waist to Hip Ratio (WHR) in the study was 77.5% among the reproductive age women of Pokhara metropolitan, Kaski district. Fruits consumption (AOR=0.488; 95% CI: 0.251-0.950) was identified as the protective factor whereas increased age (AOR =2.88, 95% CI: 1.24-6.65), physical activity (AOR=2.154; 95% CI: 1.118-4.149) and parity (AOR=1.66; 95%CI:0.60-4.61) were found to be significantly associated with abdominal obesity. Conclusion: The study demonstrates that the abdominal obesity among reproductive age women is of prime importance in Kaski district of Nepal calling for an action to educate them for lifestyle modifications.Also the concerned authorities of Pokhara metropolitan should consider this issues focusing on nutritional interventions while framing the nutritional programs.